Optimization of bolen production profits at Kes's Bakery Jambi using the simplex method based on Lindo software - Desta Dwi Ayu Lestari; Sisca Octarina; Fitri Maya Puspita (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Kes's Bakery Jambi faces challenges in selecting the most appropriate production strategy for two types of bolen, namely chocolate bolen and durian bolen, in order to maximize profits. Determining the production quantity must consider the limitations of raw materials such as flour, eggs, butter, chocolate, and durian, so it cannot be done haphazardly. This study aims to find the optimal combination of bolen production quantities to maximize profits while still considering the limitations of existing resources. The method applied is a linear program with a simplex approach. The data analyzed in this study include seven main data, namely the raw material requirements per product unit (flour, eggs, butter, chocolate, and durian), the selling price of each product, and the amount of raw material inventory available at Kes's Bakery Jambi. The analysis was conducted using the simplex method and implemented through LINDO software to obtain faster and more accurate calculation results. The research findings indicate that the optimal solution is obtained by producing 25 units of chocolate bolen and 16 units of durian bolen, resulting in the highest profit of Rp1,355. 000. These findings indicate that the application of optimization models can improve the efficiency of raw material use and support better production decisions.